Multiphase equilibria of waxy systems with predictive equations of state and a solid solution model - Nasrifar, Khashayar (Elsevier, 2012)
Abstract A thermodynamic model is developed to predict the vapor-liquid, solid-liquid, solid-vapor and solid-liquid-vapor equilibria of systems containing methane with waxy components. The model takes the advantages of equations of state to describe the vapor and liquid phases. The solid phase is described by Coutinho’s activity coefficient model, i.e., the solid phase is assumed to be orthorhombic solid solution. Impact of pressure on the solid phase is included by coupling solid-liquid Clapeyron relationship with Poynting correction factor. While no adjustable parameter is used, the model satisfactorily predicts the phase boundaries of the synthetic and real systems resembling gas condensate mixtures for wide ranges of pressure and temperature.